Ekranisasi Novel Cinta Subuh Karya Alii Farighi ke Film “Cinta Subuh” Karya Indra Gunawan - Indah Permata Sari; Muhammad Adek (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
The main objective of this research is to describe the process of ecranization of plot, setting, and characterization in reducing, adding, and changing variations from the novel to the film Cinta Subuh. This research uses descriptive method. The data sources in this study are the novel Cinta Subuh by Alii Farighi and the film Cinta Subuh by Indra Gunawan. The research instrument is the researcher himself as the main instrument using a number of formats, both for data collection and for analyzing data. The data collection technique was carried out by reading the novel Cinta Subuh by Alii Farighi then watching the film Cinta Subuh by Indra Gunawan and inventorying the data into a data inventory format and grouping data related to the form of ecranization from the novel to the film Cinta Subuh. The data analysis technique uses content analysis. This research resulted in: (1) the aspect of shrinkage, there are 52 data that occur in plot elements 40 times, setting 9 times, and characterizations of 13 characters in the novel. (2) the additional aspect is that there are 38 data that occur in the plot elements of 26 data, the background is 5 data, and the characterizations are 7 data in the film. (33) there are 15 data aspects of changing variations that occur in plot elements of 6 data, setting of 4 data, and characterizations of 5 data in the novel to the film. Changes that occur from the process of ecranizing novels to films will result in many changes due to the differences in the media used in the making of novels and films, such as differences in the process of making and enjoying them.